Experimental and numerical assessment of weld pool behavior and final microstructure in wire feed laser beam welding with electromagnetic stirring. (September 2019) - Meng, Xiangmeng; Bachmann, Marcel; Artinov, Antoni; Rethmeier, Michael
Abstract: Advantages such as element homogenization and grain refinement can be realized by introducing electromagnetic stirring into laser beam welding. However, the involved weld pool behavior and its direct role on determining the final microstructure have not been revealed quantitatively. In this paper, a 3D transient heat transfer and fluid flow model coupled with element transport and magnetic induction is developed for wire feed laser beam welding with electromagnetic stirring. The magnetohydrodynamics, temperature profile, velocity field, keyhole evolution and element distribution are calculated and analyzed. The model is well tested against the experimental results. It is suggested that a significant electromagnetic stirring can be produced in the weld pool by the induced Lorentz force under suitable electromagnetic parameters, and it shows important influences on the thermal fluid flow and the solidification parameter. The forward and downward flow along the longitudinal plane of the weld pool is enhanced, which can bring the additional filler wire material to the root of the weld pool. The integrated thermal and mechanical impacts of electromagnetic stirring on grain refinement which is confirmed experimentally by electron backscatter diffraction analysis are decoupled using the calculated solidification parameters and a criterion of dendrite fragmentation.